2010
DOI: 10.1007/s10528-010-9364-x
|View full text |Cite
|
Sign up to set email alerts
|

Allele Distributions and Frequencies of the Six Prion Protein Gene (PRNP) Polymorphisms in Asian Native Cattle, Japanese Breeds, and Mythun (Bos frontalis)

Abstract: Six polymorphic sites of the bovine prion protein gene (PRNP) were genotyped in 569 animals of Asian native cattle, Japanese breeds, purebred mythun (Bos frontalis), and mythun x cattle composite animals. At the 23-bp indel site, a deletion (23-) allele was a major allele in all populations except mythun. At the 12-bp indel site, an insertion (12+) allele was a major allele in all populations. The 14-bp indel site was polymorphic in all Asian native cattle. In the octapeptide repeat region, a six-repeat allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
9
1
Order By: Relevance
“…Conversely, in three Chinese indigenous breeds (Qinchuan, Nanyang and Jiaxian), the allele 'I' frequency was higher than allele 'D' frequency. For 12-bp indel locus, the allele 'I' frequency was higher than allele 'D' frequency in all studied breeds population, which was in contradiction to the previous reported results in US sires, Mongolia native and other cattle breeds population (Seabury et al 2004;Shimogiri et al 2010). Notably, allele 'I' at these two locus was higher in Chinese indigenous breeds, and previous reports revealed that the 12-bp insertion and 23-bp insertion polymorphisms all increased the resistance to BSE (Sander et al 2005;Juling et al 2006;Haase et al 2007;Xue et al 2008;Msalya et al 2010).…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, in three Chinese indigenous breeds (Qinchuan, Nanyang and Jiaxian), the allele 'I' frequency was higher than allele 'D' frequency. For 12-bp indel locus, the allele 'I' frequency was higher than allele 'D' frequency in all studied breeds population, which was in contradiction to the previous reported results in US sires, Mongolia native and other cattle breeds population (Seabury et al 2004;Shimogiri et al 2010). Notably, allele 'I' at these two locus was higher in Chinese indigenous breeds, and previous reports revealed that the 12-bp insertion and 23-bp insertion polymorphisms all increased the resistance to BSE (Sander et al 2005;Juling et al 2006;Haase et al 2007;Xue et al 2008;Msalya et al 2010).…”
Section: Discussioncontrasting
confidence: 99%
“…Given the low frequency of the 14-bp indel within the 3 0 UTR in cows and artificial insemination sires of the USA (0.006 and zero, respectively), 23 in Vietnamese native cattle (0.18) and Laos native populations of Asian origin (0.22) 27 (Table 1), we hypothesized that the frequency of the 14-bp indel of the 3 0 UTR in PRNP gene may be low in Chinese cattle breeds. We used an ME strategy to detect the allele frequency in all individuals.…”
Section: Discussionmentioning
confidence: 99%
“…10,28 However, they did not corroborate the results presented by Shimogiri, 10 who reported the frequency in Japanese Brown of more than 0.10. 27 Those discrepancies might be due to the small sample size (n D 64). Overall, the 14-bp indel within the PRNP gene was characterized by low frequency in main Chinese cattle breeds.…”
Section: Discussionmentioning
confidence: 99%
“…The E211K change is analogous to the human E200K amino acid replacement, which is a trigger of the development of heritable human TSE [8]. Recently, new information regarding the frequency and distribution of bovine PRNP indel polymorphisms has been reported for Vietnamese local cattle and native Chinese cattle [17, 27, 29], and the information suggests that Asian local breed cattle have a variety of genetic divergences within the PRNP for potential association with BSE.…”
mentioning
confidence: 99%